ISSR molecular markers and anatomical structures can assist in rapid and directional screening of cold-tolerant seedling mutants of medicinal and ornamental plant in Plumbago indica L. - Li, Yirui; Cheng, Xu; Lai, Junlin; Zhou, Yunzhu; Lei, Ting; Yang, Lijuan; Li, Jiani; Yu, Xiaofang; Gao, Suping (Frontiers in Plant Science, 2023)
Plumbago indica L. is a perennial herb with ornamental and anticancer medicinal functions widely distributed in the tropics. It is affected by temperature and cannot bloom normally in colder subtropical regions, which seriously affects its ornamental value. To create low-temperature tolerant mutants and enrich new germplasm resources, this study used tissue culture and chemical reagent (NaN3) and low-temperature stress induction to target and screen for cold-tolerant mutants. The results showed that the ISSR band polymorphism ratio of the 24 suspected mutant materials was 87.5%. The DNA profiles of the 9 mutants initially identified were altered. There are major differences in the anatomical structures of roots, stems and leaves. The mutants mostly exhibited reduced root diameter, increased stem diameter, enlarged leaf pulp cells, increased thickness and high specificity, which were presumed to be important for the mutants to acquire different cold tolerance. Using 0°C as the low temperature stress treatment temperature, the four screened cold-tolerant mutants showed slower leaf wilting, higher light energy conversion efficiency, less MDA content accumulation, and more soluble sugar and proline content accumulation in response to low temperature. These characteristics are consistent with the response of cold-tolerant plants to low temperature. This study provides a more rapid and accurate technique for identifying and screening cold-tolerant mutants, and lays the foundation for future experiments on the creation of new cold-resistant varieties.